UNA INQUIETANTE EXTRAÑEZA: LA VISIÓN DE LA ESPAÑA DEL AÑO 1808 EN LOS TESTIMONIOS NAPOLEÓNICOS, ENTRE LA ALIANZA DESIGUAL Y LA GUERRA ABIERTA - Lafon, Jean-Marc (Anales de Filología Francesa, 2008)
Readings from the testimonies (diaries on the march, letters, memoirs) by imperial officers and soldiers of the French Empire who entered the Peninsula between autumn 1807 and spring 1808 reveal how perplexed and disconcerted they were almost as soon as they crossed the border. Their view broadly backs up that of the 18th century travellers from abroad, emphasising once again the economic and cultural backwardness of Spain. However, some new notes also appear in these texts that bear witness to a new pre-romantic sensitivity. Above all, these readings allow us to detail the decline in the relations between the “official allies” and cast new light on the reasons for the failure of the Napoleonic venture during the summer of 1808.